NERACA PERDAGANGAN (BALANCE OF TRADE), NERACA PEMBAYARAN (BALANCE OF PAYMENT) DAN PINJAMAN NEGARA - Ahmad Wahyudi Zein; Cici Mutia Siregar; Muhammad Haykal; Sofia Damayanti Hasibuan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This journal examines the intrinsic relationship between the balance of trade, balance of payments, and government debt as key components of a national economy. The balance of trade (surplus or deficit) is a critical part of the balance of payments, which reflects all economic transactions between a country and the rest of the world. When the balance of payments experiences a long-term deficit, countries often rely on government debt to cover the shortfall-though this also poses risks of increasing debt burdens. This study analyzes the mechanism of their interrelationship, positive and negative impacts, and policy implications for maintaining economic stability, with a concrete case study of Indonesia between 2004-2023 to illustrate these dynamics in practice.